Involving English Extracurricular Activities To Improve Students’ Speaking Skills - Manuas, Maissy (Journal of English Language Teaching, Literature and Culture, 2022)
This study aimed at the effectiveness of English extracurricular activities for the improvement of the students’ speaking skill based on gender and age. The researcher adapted the questionnaire from Fatash (2008). This study was conducted in SMA X and has involved 105 respondents from grade 10, 11, and 12 of IPA and IPS. The result showed that the students’ perception of their involvement in English extracurricular activities was found to be 3.83 which indicates as highly involved. Then, the result also showed that there was a significant difference in the students’ perception of their involvement in English extracurricular activities based on gender since it was found to be .000. It meant that male and female students have different perception of English extracurricular activities. Lastly, the result showed that there was no significant difference in the students’ perception of involving the English extracurricular activities based on age since it was found to be .50. It meant that students from all range of ages have the same perception of being involved in English extracurricular activities.